Sensors and Actuators in Smart Cities - Mounir Arioua (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Cities across the globe are installing sensors and actuators to become more sustainable, safe, efficient, and greener, with the hope of improving urban life. This book examines how sensors and actuators enable smart cities to provide critical services from road traffic management and disaster preparedness to key infrastructure, e.g., healthcare, and public safety. It presents a systems engineering perspective of the foundations and principles that span the various challenges and opportunities of developing smart cities. In addition, the studies presented in this book give the state of the art, system design, use cases, simulation, and real-life deployments or testbeds. The comprehensiveness of this book pose it as a reference for researchers and practitioners working on building the future smart cities and applications.